MANAJEMENMUSYAWARAH GURU MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN DALAM MENINGKATKAN PROFESIONALISME GURU SMP - Fahnur Desiawati (Manajer Pendididikan, 2016)
The objective of this research was to describe the management the subject teachers forum Pkn The collected data analize with justify standard criteria descriptive. The result showed In the preparation of syllabus, Subject Teacher Forum was instrumental in adjust the curriculum to the conditions on the ground Implementation of Subject Teacher Forum junior levelBengkulu City. Improved curriculum based on the syllabus. Monitoring and evaluation of the implementation of activities preparation of study planning at the Subject Teacher ForumBengkulu City is by Subject Teacher Forum’s make study planning guided by the curriculum and syllabus of existing ones. As for repair activities preparation of study planning Trustees Trustees Subjects derived from the Department of Education.Keywords: teaching media, curriculum, sylabus, monitoring and evaluation.